Experimental study on the evolutionary characteristics of acoustic signals produced by granite under biaxial compression with different intermediate principal stresses - Lu, Yongsong; Li, Peifeng; Cai, Wei (Frontiers in Earth Science, 2023)
Biaxial compression is a typical stress state experienced by the surrounding rock near the excavation boundaries under deep underground engineering, frequently resulting in engineering geological disasters (spalling and rockburst). The motivation to mitigate the risk and damage of these disasters has led us to compressively examine the evolutionary characteristics of acoustic signals (microseismic (MS) events, sound and acoustic emission (AEs)) produced by granite under biaxial compression with different intermediate principal stresses. These characteristics include time (activeness and b value) and frequency (main frequency and proportion of the advantage frequency bands) domains. The results suggest that: (1) the signal properties-driven order of activeness under low and high intermediate principal stresses for the initial stresses were as follows: AE accounted for 37.4% and 43.5% of σpeak, MS for 61.1% and 66% of σpeak, and sound for 81.8% and 85.5% of σpeak. (2) The notable distinction in precursors of different acoustic signals before granite failure was confirmed: the sequential relationship in the continuous decrease rate of the b value (AE < MS < sound), the occurrence (only existing in AE signals) of a few signals with extremely high amplitude (the 'quiescent period') and the different frequency-change rule in the proportion of the advantage frequency bands. (3) The strong influences of intermediate principal stress on the signal precursors were determined; these precursors in the activeness, b value, and proportion are negative to intermediate principal stress, whereas that of the main frequency shows a positive correlation. Consequently, these findings can contribute integrated usage of the multifrequency signals in the prediction and warning of geological disasters under deep underground engineering.